Congenital Diaphragmatic Hernia with Intrathoracic Renal Ectopia: Thoracoscopic Approach for a Complete Anatomical Repair - Colin Mizzi; David Farrugia; Muhammad S. Choudhry (Georg Thieme Verlag KG, 2020)
Congenital diaphragmatic herniae (CDH) with associated intrathoracic ectopic kidneys are rare congenital anomalies, with a reported incidence of only 0.25%. The authors report a case of a 24-day-old baby girl who was diagnosed with a left-sided CDH on a chest X-ray taken for pneumonia. Computed tomography scan showed CDH hernia, containing small and large bowel and whole left kidney with adrenal gland. Thoracoscopic reduction in the bowel, kidney, and adrenal gland into the abdomen and primary closure of the defect was achieved with no complications. During investigation of the child, it was discovered that her maternal aunt had also had a left-sided congenital diaphragmatic hernia containing the kidney, which was treated via open surgery after birth; she subsequently developed renal cell carcinoma and required radical nephrectomy of that kidney during her third decade.